Purchase Intention Mediates Factors Influencing The Purchase Decision of Coffee Shop Consumers in Denpasar, Bali - Permadi, I Made Billy; Lestari, Ni Putu Nina Eka (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
Business can be defined as an activity that uses resources to produce goods and services that consumers need or want. As time goes by, the business world is becoming more competitive which ultimately encourages more and more businessmen to innovate to achieve their company goals. The role of purchase intention mediates the influence of store atmosphere, service quality and E-WOM on the purchase decision of coffee shop consumers in Denpasar City. The population used in this study is coffee shop consumers in Denpasar City. The sampling technique that will be used in this study is purporsive sampling. The researcher chose 150 people as respondents. In this study, the inferential statistics used are PLS-based SEM analysis. The results of the study found that Store atmosphere had a positive and significant effect on buying interest. The quality of service has a positive and significant effect on buying interest. E-WOM has a positive and significant effect on buying interest. Store atmosphere has a positive and significant effect on purchase decisions. Service quality has a positive and significant effect on purchase decisions. E-WOM has a positive and significant effect on purchase decisions. Buying interest has a positive and significant effect on purchase decisions. Buying interest is able to partially mediate the influence of store atmosphere on purchase decisions. Buying interest is able to partially mediate the influence of service quality on purchase decisions. Buying interest is able to partially mediate the influence of E-WOM on purchase decisions.